Computed tomography morphological assessments of central airways in interstitial lung abnormalities and idiopathic pulmonary fibrosis - Maetani, Tomoki; Tanabe, Naoya; Tanizawa, Kiminobu; Sakamoto, Ryo; Shiraishi, Yusuke; Hayashi, Yusuke; Uyama, Michihiro; Matsunashi, Atsushi; Sato, Susumu; Suzuki, Katsuhiro; Masuda, Izuru; Fukui, Motonari; et al. (Respiratory research, 2024)
Background Little is known about whether central airway morphological changes beyond traction bronchiectasis develop and affect clinical outcomes in patients with idiopathic pulmonary fibrosis (IPF). This study aimed to compare central airway structure comprehensively between patients with IPF, subjects with interstitial lung abnormality (ILA), and those without ILA (control) using computed tomography (CT). We further examined the prognostic impact of IPF-specific CT airway parameters in patients with IPF. Methods This retrospective study included male patients with IPF, and male health checkup subjects divided into those with ILA and control based on lung cancer screening CT. Using an artificial intelligence-based segmentation technique, the extent of fibrotic regions in the lung was quantified. After airway tree segmentation, CT parameters for central airway morphology, including the lumen area of the extrapulmonary airways (LA extra ), wall and lumen area of the segmental/subsegmental intrapulmonary airways (WA intra and LA intra ), tracheal distortion (tortuosity and curvature) and bifurcation angle of the main carina, were calculated. Results There were 106 patients with IPF, 53 subjects with ILA, and 1295 controls. Multivariable models adjusted for age, height and smoking history revealed that LA intra and WA intra were larger in both ILA and IPF, and that tracheal tortuosity and curvature were higher in IPF, but not in ILA, than in the control, whereas the bifurcation angle did not differ between the 3 groups. According to multivariable Cox proportional hazards models including only patients with IPF, increased WA intra was significantly associated with greater mortality (standardized hazard ratio [95% confidence interval] = 1.58 [1.17, 2.14]), independent of the volume of fibrotic regions, normal-appearing regions, or the whole airway tree in the lung. Conclusion Increased lumen area and wall thickening of the central airways may be involved in the pathogenesis of ILA and IPF, and wall thickening may affect the prognosis of patients with IPF.